A CODE MIXING USAGE ON SOCIAL MEDIA: A LINGUISTIC ANALYSIS OF VIDEO ON TIKTOK - Nurchurifiani, Eva; Hanum, Innayah; Damiri, Adenan; Oktariyani, Oktariyani (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2025)
Code mixing is a common strategy in communicating among person who learn or use more than one language. This research has aimed to focus on analysing variety types and reasons of code-mixing used in Fathia Fairuza’s TikTok video. The study uses a descriptive qualitative to report and describe the result of analysis data. Theory by Hoffman was used to classify types which are intra-sentential, intra-lexical, and involving change of pronunciation. Hoffmans’ theory about motivation in using code-mixing was used in this study that includes talking about particular topic, quoting somebody else, being emphatic about something, interjection, and repetition used for clarification. The subject data in this study is Fathia Fairuza’s utterances on her TikTok video. This study has found that the most used type of code-mixing was intra-sentential, and intention of clarifying the speech content for interlocutor as the common reason. This study was aimed to bring knowledge about kind of code-mixing and motivation or purpose in using code-mixing on TikTok video.